Education and Territory: A Conceptual Framework - Champollion, Pierre (2015)
The links between education and territory are complex. No part of schooling can free itself from the territorial context in which the school action plan develops: formal schooling, academic achievement, vocational orientation, didactics, pedagogy, etc. are all concerned, to a greater or lesser extent according to the territories and to the educational systems. Thus, territory can have an effect from the outside on school education as an impact factor, but it can also have a full educational role. It may also impact on education as a whole, as in some mountain areas. Nevertheless, all things considered, is it really the territory which has an impact on school; or is it rather its «symbolic » part-the territoriality-which «shapes» the education pathways? While the different contexts having influence on education-spatial, political, institutional contexts for instance-have been analysed for a long time, it is completely different regarding territoriality, which has only really been tackled for fifteen years.